STRATEGI PENGEMBANGAN USAHA DALAM MENGHADAPI TINGGINYA HARGA BAHAN BAKU PADA PRODUSEN TAHU SUMBER BERKAH DESA KLITIK, KECAMATAN GENENG KABUPATEN NGAWI - Zaky Sarmada; Suryo Prayogo (Fakultas Ekonomi Bisnis Islam, 2022)
The toughest challenge for tofu producers is the price of raw materials, namely soybeans, whose prices are unstable and tend to rise recently. not only to survive but also to develop. The increase in the price of soybeans has had a major impact on tempeh, tofu, and other processed products made from soybeans. The Sumber Berkah tofu industry is one of the businesses that process soybeans into tofu that is ready for sale. So that the increase in soybean prices greatly affects the sustainability of this tofu industry business. The Sumber Berkah tofu industry was founded in 2003 and is located in Sambirobyong Hamlet, Klithic Village, Ngawi Regency. This home industry supplies the tofu needs of some Ngawi people and its surroundings and hassurvived to this day. Based on this, the author wants to examine how the business development strategy and what did the Sumber Berkah tofu producerdo in Klitik Village, Geneng District, Ngawi Regency in the face of high raw material prices. The results of this study are that the strategy adopted bySumber Berkah tofu producers in responding to rising soybean prices is to reduce the size of their tofu production, and according to the author, SumberBerkah tofu producers can apply cost leadership strategies and differentiation strategies so that their business can further develop.